Festschrift für Prof. Dr. Karl-Heinz Möller - Ratzel, Rudolf; Frister, Helmut (Nomos Verlagsgesellschaft mbH & Co. KG, 2023)
With this ‚Festschrift‘ friends, colleagues and companions from academia and legal practice honour Prof. Dr. Karl-Heinz Möller on the occasion of his 70th birthday. The jubilarian is a specialist lawyer for medical law, mediator and honorary professor at Heinrich-Heine University. The law firm he founded is one of the most renowned in Germany in the field of health care. In a total of 34 articles, the authors address current topics from the anniversary's specialist area, in particular medical contract and professional law, hospital law, reproductive medicine and (medical) criminal law. With contributions byRA Dr. Stefan Bäune, FAMedR | RA Prof. Dr. Franz-Josef Dahm, FAMedR u FAVerwR | RA Dr. Matthias Dann, LL.M. | RA Dr. Alexander Dorn; FAMedR u FAStrafR | RA Nurettin Fenercioglu, LL.M. | Prof. Dr. Helmut Frister | RA Dr. Torben Götz, FAMedR | RA Hannes Hasselbach, LL.M. | Notarass. Dr. Moritz Jäschke | RA VizePräsSG a.D. Detlef Kerber | StB Thomas Ketteler-Eising | RA Dr. Rainer Kienast, FAArbR | RA Christian Krapohl, FAMedR u FAArbR | RAin Dr. Maja Lehmann | RA Michael Lennartz | Prof. Dr. Katharina Lugani | RA Dr. Kyrill Makoski, LL.M. (Boston Univ.), FAMedR | RA Dr. Christian Maus, FAMedR | Dr. Andreas Meschke, FAMedR | StB Dr. Rolf Michels | Prisca Napp-Saarbourg | RA Dirk Niggehoff, FAMedR | RA Peter Peikert | RA Prof. Dr. Hermann Plagemann, FAMedR u FASozR | RA Reinhold Preißler, FAMedR | RAin KerstinRadtke-Schwenzer, FAMedR u FASozR | RA Dr. Rudolf Ratzel, FAMedR | RA Prof. Dr. Martin Rehborn, FAMedR | RA Dr. Valentin Saalfrank, FAMedR | RAin Dr. Kerrin Schillhorn, MIL, FAMedR u FAVerwR | Ltd. MinR Prof. Dr. Frank Stollmann | RA Gerrit Tigges, FAMedR | RA Prof. Dr. Michael Tsambikakis, FAMedR u FAStrafR | RA Prof. Dr. med. Dr. jur. Thomas Ufer, FAMedR | RA Rüdiger Weidhaas, FAStrafR | RAin Dr. habil. Sabine Wesser | RA Prof. Dr. Jürgen Wessing, FAStrafR | RA Harald Wostry, FAMedR u FAStrafR | AkadR a.Z. Dr. Thomas Wostry | RA u Mediator Dr. Ole Ziegler, FAMedR u FAHuGR